Choreomata: Performance and Performativity after AI - Trillo, Roberto Alonso 1983-; Poliks, Marek (2024)
Is artificial intelligence (AI) becoming more and more expressive, or is human thought adopting more and more structures from computation? What does it mean to perform oneself through AI, or to construct one’s subjectivity through AI? How does AI continue to complicate what it means to have a body? Has the golden age of AI, especially with regards to creative applications, already ended?Choreomata: Performance and Performativity after AI is a book about performance and performativity, but more specifically, it is a book about the performance of artificiality and the performance of intelligence. Both humans and human-designed computational forces are thoroughly engaged in an entangled, mutual performance of AI. Choreomata spins up a latticework of interdisciplinary thought, pairing theoretical inquiry from philosophy, information theory, and computer science with practical case studies from visual art, dance, music, and social theory.Through cross-disciplinary proportions and a diverse roster of contributors, this book contains insights for computer scientists, social scientists, industry professionals, artists, and beyond.
Foreword by Tiziana Terranova -- Preface -- List of Contributors -- A. Performing Artificiality, Performing Intelligence -- Subjectivity; 0-Degree Plane of Neuroelectronic Continuity: AI & Psychosocial Evaporation / Marek Poliks & Roberto Alonso Trillo -- 2. Performing the Automated Image / Anna Munster & Ned Rossiter -- 3. Negative Aesthetics: AI and Non-Performance / Luciana Paris -- 4. Performance, Performativity, and Subjectivity at the Intersection of Art and Digital Cultures / Barbara Bolt -- Creativity; 5. Performing Creativity: Text-to-Image Synthesis and the Mimicry of Artistic Subjectivity / Keith Tilford -- 6. Galatea Reloaded: Imagination Inside-Out Imagine / Reza Negarestani -- Representation; 7. Intelligent Company: Co-creative AI as Anamnesis / Jonathan Impett -- 8. Autonomy, Intention, Performativity: Navigating the AI Divide / Jon McCormack -- 9. Interaction Grammars: Beyond the Imitation Game / AA Cavia -- B. Choreomatic Bestiary: Encounter; 10. Choreomata / Sofian Audry -- 11. The Musicality of Imperfection / Davor Vincze -- 12. Robot Choreography, Choreorobotics, and Humanist Technology: A Conversation between Dr. Madeline Gannon and Dr. Ken Goldberg / Catie Cuan -- Proliferation; 13. Ars Autopoetica: On Authorial Intelligence, Generative Literature, and the Future of Language / Sasha Stiles -- 14. AI, Architecture, and Performance: Walt Disney Concert Hall Dreams / Refik Anadol & Pelin Kivrak -- 15. Performing AI-Generated Theater Plays / Klára Vosecká & Tomáš Musil & Rudolf Rosa -- Annihilation; 16. Identity Dissolution: Using Artificial Intelligence for Artistic Exploration of Identity Models -- Alexander Schubert -- 17. Noise and Subjectivity in the Era of Machine Learning / Mattin -- After-Body; 18. Descendent: AI and the Body beyond Hybridization / Roberto Alonso Trillo -- 19. Descendent: Understanding the Digital Production Process from Human Interpretation to Algorithmic Interpolation to AI Inference / Peter Nelson -- 20. Ghosts of the Hidden Layer -- People & Things / Jennifer Walshe -- Index
Keywords: Artificial intelligence; Performance; Music philosophy and esthetics